The Influence of Knowledge, Experience, and Motivation on Tutor Performance in PKBM Gegesik - Hidayat, Asep Ronny; Bahari, Yogi; Sutarjo, Sutarjo; Sihabudin, Sihabudin (Lembaga Teewan Journal Solutions, 2026)
This research was conducted at Community Learning Activity Centers (PKBM) in the Gegesik District area, Cirebon Regency. The purpose of this study was to examine and analyze the influence of knowledge, experience, and motivation on tutor performance, measured both partially and simultaneously. This research was based on the fact that tutor performance in the research area had not shown optimal results, which was caused by the lack of optimal knowledge, work experience, and motivation possessed by the tutors. This study was categorized as descriptive and verificative research. The method used was an explanatory survey. The research population consisted of teachers, and the sampling technique was conducted using cluster proportional random sampling. The sources of data in this study were primary and secondary data. The data analysis technique used was path analysis. The results showed that the knowledge factor influenced performance by 7.31%. The findings also proved that work experience had a positive and significant effect on performance by 43.29%. Furthermore, motivation had a positive and significant influence on teacher performance by 35.63%. Simultaneously, knowledge, work experience, and motivation influenced performance improvement by 86.23%, while the remaining 13.77% was influenced by other variables outside the scope of this study.